2007
DOI: 10.1086/523276
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Risk Factors Associated With Isolation of Linezolid-Resistant Strains of Vancomycin-Resistant Enterococcus

Abstract: objective. To identify independent risk factors associated with isolation of linezolid-resistant, vancomycin-resistant Enterococcus (VRE).design. A retrospective, case-case-control study.setting. A tertiary care, academic medical center.methods. VRE isolates from clinical cultures were retrospectively analyzed for linezolid resistance during our 18-month study period. Clinical data were obtained from electronic patient records, and the risk factors associated with isolation of linezolid-resistant VRE were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…To overcome the limitations inherent in the two different types of control groups, two variations on the case-control design have been developed: case-case-control (23,33,(111)(112)(113)(114)(115)(116)(117)(118)(119)(120) and casecontrol-control (121-126). As described by Kaye et al (40), a casecase-control study involves two separate analyses: (i) a comparison of cases with a resistant strain of an organism to controls uninfected by that organism and (ii) a comparison of cases with a susceptible strain of the organism to those same controls.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…To overcome the limitations inherent in the two different types of control groups, two variations on the case-control design have been developed: case-case-control (23,33,(111)(112)(113)(114)(115)(116)(117)(118)(119)(120) and casecontrol-control (121-126). As described by Kaye et al (40), a casecase-control study involves two separate analyses: (i) a comparison of cases with a resistant strain of an organism to controls uninfected by that organism and (ii) a comparison of cases with a susceptible strain of the organism to those same controls.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…An open-label, nonrandomized study showed linezolid to cause microbiologic eradication rate of 85% in VR E. faecalis bacteremia [56]. Reports of linezolid resistance among VRE isolates are emerging, with up to 20% resistance being reported in certain institutions, commonly among urine isolates [57].…”
Section: Newer Agentsmentioning
confidence: 99%
“…Studies evaluating linezolid for the treatment of vancomycin-resistant E. faecium bloodstream infection (BSI) have revealed clinical success frequencies ranging from 58% to 78% (7,8). However, reports of linezolid resistance in VRE have emerged, with an incidence as high as 20% (9). Moreover, prolonged treatment with linezolid can lead to myelosuppression, including neutropenia, thrombocytopenia, and anemia, which are frequent comorbid conditions already present in many patients with VRE infections (6,10).…”
mentioning
confidence: 99%